Implementasi Robot Lengan Pemindah Barang 3 DOF Menggunakan Metode Inverse Kinematics - Rimas Oktama; Rizal Maulana; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Moving object process from one place to another is usually done with the conventional way using human power, then it can certainly getting heavy objects and the farther the distance of displacement, manpower required objects are also getting bigger. It is judged ineffective considering the limitations of human capability in the shift of weight and time limitations of humans in the work. Based on these problems required a robot arm that is able to moving an object from one place to another. The robot arm was designed to have 3 DOF (Degree of Freedom) and the whole joint is revolute and implemented using servo dynamixel AX-12A. Input from this robot is initial coordinates and final coordinates are then computing by the method of inverse kinematics with an output in the form of large angle of each joint required in order for the robot arm reaches the point coordinates. Results from research that has been done, the robot is able to move the object from one point coordinate to another within an average period of 6 to 7 seconds as well as the level error that occurred in the achievement of the desired angle of 0.64%. Based on the results of the implementation system of the arm robot assessed transporter 3DOF using inverse kinematics method is very effective in carrying out its functions to move an object.